Impact of a United Kingdom-wide campaign to tackle antimicrobial resistance on self-reported knowledge and behaviour change. (December 2016) - Chaintarli, Katerina; Ingle, Suzanne; Bhattacharya, Alex; Ashiru-Oredope, Diane; Oliver, Isabel; Gobin, Maya
Abstract Background As part of the 2014 European Antibiotic Awareness Day plans, a new campaign called Antibiotic Guardian (AG) was launched in the United Kingdom, including an online pledge system to increase commitment from healthcare professionals and members of the public to reduce antimicrobial resistance (AMR). The aim of this evaluation was to determine the impact of the campaign on self-reported knowledge and behaviour around AMR. Methods An online survey was sent to 9016 Antibiotic Guardians (AGs) to assess changes in self-reported knowledge and behaviour (outcomes) following the campaign. Logistic regression models, adjusted for variables including age, sex and pledge group (pledging as member of public or as healthcare professional), were used to estimate associations between outcomes and AG characteristics. Results 2478 AGs responded to the survey (27.5 % response rate) of whom 1696 (68.4 %) pledged as healthcare professionals and 782 (31.6 %) as members of public (similar proportions to the total number of AGs). 96.3 % of all AGs who responded had prior knowledge of AMR. 73.5 % of participants were female and participants were most commonly between 45 and 54 years old. Two thirds (63.4 %) of participants reported always acting according to their pledge. Members of the public were more likely to act in line with their pledge than professionals (Odds Ratio (OR) =3.60, 95 % Confidence Interval (CI): 2.88-4.51). Approximately half of participants (44.5 %) (both healthcare professionals and members of public) reported that they acquired more knowledge about AMR post-campaign. People that were confused about AMR prior to the campaign acquired more knowledge after the campaign (OR = 3.10, 95 % CI: 1.36-7.09). More participants reported a sense of personal responsibility towards tackling AMR post-campaign, increasing from 58.3 % of participants pre-campaign to 70.5 % post-campaign. Conclusion This study demonstrated that the campaign increased commitment to tackling AMR in both healthcare professional and member of the public, increased self-reported knowledge and changed self-reported behaviour particularly among people with prior AMR awareness. Online pledge schemes can be an effective and inexpensive way to engage people with the problem of AMR especially among those with prior awareness of the topic.